PERLINDUNGAN SAKSI DAN KORBAN MENURUT UNDANG-UNDANG NOMOR 31 TAHUN 2014 - Suryani Yusi; Renol Ababil (Fakultas Hukum Universitas IBA Palembang, 2019)
Witnesses and victims are very important in revealing a case in the justice system in Indonesia. The most important issue is crime crime; corruption, narcotics, rape and other cases. But in reality, witnesses and victims get positions in the unfavorable, who feel afraid, or get pressure from certain parties so they choose to be quiet and not report the events they have experienced. Seeing these conditions, as a professional institution, the Witness and Victim Protection Agency (LPSK) carries the responsibility of providing assistance and assistance to witnesses and victims in accordance with their duties and authorities governing Article 12 of Law Number 31 Year 2014.